Implementation of the Zoning System Policy in Equalising the Number of New Learners at SMP Mataram City in 2024 - Hardiansyah, Hardiansyah; Sigap, Sigap; Budiyanto, Budiyanto; Hazin, Mufarrihul (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2025)
Abstract: Basically, zoning itself is a development of rayonation, when rayonation is a division of territory based on agreement, then zoning emphasizes more on the division of territory according to its function and management objectives. In the education zoning system, the function and purpose of management is to accelerate the equalization of education quality in Indonesian educational units. The emergence of superior schools and outlying schools in Indonesia is due to the selection of the quality of prospective students in accepting new students. One of the government's efforts to improve and equalize quality education is to implement a zoning system for accepting new students. Through the zoning system, students who live close to schools have a better chance of being accepted at educational units. The provisions of the zoning system according to Permendikbud No. 14 of 2018 are the priorities of prospective students (junior high school and high school) who must be accepted including: first, the distance from residence to school according to zoning provisions; second, domicile or transfer of family card; and third, academic and non-academic achievements. Meanwhile, the zoning system is the second consideration for the elementary school level after the minimum age factor for entering school has been met. The formulation of the problem in this study is: (1) What is meant by the Zoning System, (2) How is the implementation of the Zoning System policy in Mataram City Middle Schools, (3) What is the impact of the Zoning System policy on the distribution of the number of new students in Mataram City Middle Schools. Meanwhile, the objectives of the study to be achieved are: (1) To find out the objectives of the zoning system, (2) Describe and analyze the implementation of the zoning system policy in Mataram City Middle Schools, (3) Identify and analyze the impact of the zoning system policy on the distribution of the number of new students in Mataram City Middle Schools. Based on the results of the study, it show that the zoning system in Mataram City is still not optimal in providing equal access to education. As a result, schools in Mataram City, especially in Ampenan District and Sekarbela District, still have many students in shortage.Key Words: Zoning System Policy, Equalizing, Students